2013
DOI: 10.1148/rg.335125214
|View full text |Cite
|
Sign up to set email alerts
|

Response Criteria in Oncologic Imaging: Review of Traditional and New Criteria

Abstract: There has been a proliferation and divergence of imaging-based tumor-specific response criteria over the past 3 decades whose purpose is to achieve objective assessment of treatment response in oncologic clinical trials. The World Health Organization (WHO) criteria, published in 1981, were the first response criteria and made use of bidimensional measurements of tumors. The Response Evaluation Criteria in Solid Tumors (RECIST) were created in 2000 and revised in 2009. The RECIST criteria made use of unidimensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
170
1
7

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 256 publications
(179 citation statements)
references
References 29 publications
1
170
1
7
Order By: Relevance
“…Only patients with clinically complete or partial response according to WHO criteria (Tirkes et al,2013) and revealed recurrence or disease progression during the follow up time were included.…”
Section: Methodsmentioning
confidence: 99%
“…Only patients with clinically complete or partial response according to WHO criteria (Tirkes et al,2013) and revealed recurrence or disease progression during the follow up time were included.…”
Section: Methodsmentioning
confidence: 99%
“…Radyoterapi sonrası erken tedavi cevabının değerlen-dirilmesinde perfüzyon BT faydalı bir yöntemdir [15][16][17]. [18][19][20]. RECIST 1,1 ve 1,0'daki farklar Tablo 2'de sunulmuştur.…”
Section: Radyoterapi Sonrası Değerlendirmeunclassified
“…Necrosis as the sole indicator of a therapeutic response is observed in the case of HCC, among others; this carcinoma frequently responds only with a change in tumor vascularization to targeted systemic (e. g. sorafenib) or minimally invasive therapies, such as transcatheter arterial chemoembolization (TACE) or selective internal radiation therapy (SIRT) [19,20]. In order to meet this problem adequately, the European Association for the Study of the Liver (EASL) developed criteria published in 2001, based on two-dimensional measurements of vital tumor components, i. e. the areas that accumulate contrast media in the arterial phase [21].…”
Section: Hepatocellular Carcinoma (Hcc): Easl Mrecist and Reciclmentioning
confidence: 99%